2018
DOI: 10.5812/semj.64073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Gamma Glutamyl Transferase Levels in Diabetic Patients With and Without Retinopathy

Abstract: Background: Gamma glutamyl transferase (GGT) is a liver enzyme that is involved in oxidative stress. The association between GGT levels and diabetes complications such as microalbuminuria, retinopathy, and peripheral polyneuropathy is a challenging subject. Objectives: In this study we compared GGT levels in orally treated DM type 2 patients with and without retinopathy. Methods: In this cross-sectional study that was done between the years of 2011 and 2012, 208 patients with Type 2 DM, aged 30 -86 years old, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“… 25 The role of oxidative stress in the development of diabetes-related complications is unclear; some studies found associations with peripheral neuropathy and retinopathy. 34 35 Although the Framingham offspring study developed a simple predictive model, the use of a parental history of diabetes is challenging. Parental history of diabetes is asked in routine clinical settings, but its availability in research appears to be limited.…”
Section: Discussionmentioning
confidence: 99%
“… 25 The role of oxidative stress in the development of diabetes-related complications is unclear; some studies found associations with peripheral neuropathy and retinopathy. 34 35 Although the Framingham offspring study developed a simple predictive model, the use of a parental history of diabetes is challenging. Parental history of diabetes is asked in routine clinical settings, but its availability in research appears to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Có mối liên quan giữa stress oxy hóa, hiện tượng viêm và rối loạn chức năng tế bào β của tiểu đảo tụy, quá trình này kéo dài dẫn đến rối loạn glucose huyết [1]. Hơn nữa, tăng hoạt độ GGT thường gặp ở bệnh nhân ĐTĐ có biến chứng và ĐTĐ không kiểm soát được nồng độ glucose [2], [5]- [7]. Vậy, liệu hoạt độ GGT ở BN ĐTĐ type 2 thay đổi như thế nào?…”
Section: đặT Vấn đềunclassified
“…Tác giả Krishnamurthy (2019) đã nghiên cứu về hoạt độ GGT huyết tương ở 35 người khỏe mạnh, 35 bệnh nhân ĐTĐ type 2 kiểm soát tốt nồng độ glucose và 35 bệnh nhân ĐTĐ không kiểm soát tốt nồng độ glucose, kết quả nghiên cứu cho thấy hoạt độ GGT tương ứng ở các nhóm là 17,14±2,3 U/L; 25,17±1,8 U/L; 28,84±2,1 U/L, với p<0,05. Có mối tương quan thuận giữa hoạt độ GGT huyết tương với chỉ số BMI (R 2 =0,51), HbA1C huyết tương (R 2 = R2=0,47) [5]. Hoạt độ GGT và tỷ lệ tăng hoạt độ GGT huyết tương ở nhóm BN ĐTĐ có biến chứng mắt tương ứng là 44,3 ± 20,2 U/L; 61,5% cao hơn có ý nghĩa so với nhóm BN ĐTĐ không có biến chứng mắt là 29,7 ± 14,2 U/L, 10,4% [4].…”
Section: Bàn Luậnunclassified